Cytoplasmic Dynein Heavy Chain 1b Is Required for Flagellar Assembly in Chlamydomonas - Porter, Mary E. (The American Society for Cell Biology, 1999)
A second cytoplasmic dynein heavy chain (cDhc) has recently been identified in several organisms, and its expression pattern is consistent with a possible role in axoneme assembly. We have used a genetic approach to ask whether cDhc1b is involved in flagellar assembly in Chlamydomonas. Using a modified PCR protocol, we recovered two cDhc sequences distinct from the axonemal Dhc sequences identified previously. cDhc1a is closely related to the major cytoplasmic Dhc, whereas cDhc1b is closely related to the minor cDhc isoform identified in sea urchins, Caenorhabditis elegans, and Tetrahymena. The Chlamydomonas cDhc1b transcript is a low-abundance mRNA whose expression is enhanced by deflagellation. To determine its role in flagellar assembly, we screened a collection of stumpy flagellar (stf) mutants generated by insertional mutagenesis and identified two strains in which portions of the cDhc1b gene have been deleted. The two mutants assemble short flagellar stumps (<1–2 μm) filled with aberrant microtubules, raft-like particles, and other amorphous material. The results indicate that cDhc1b is involved in the transport of components required for flagellar assembly in Chlamydomonas.